The influence of age and sex in sarcoidosis. Issue 4 (July 2022) - Singha, Arindam; Kirkland, Marina; Drake, Wonder; Crouser, Elliott D
Abstract : Purpose of review: This review aims to describe how the clinical manifestations of sarcoidosis may be shaped by the effects of sex hormones and by age dependent changes in immune functions and physiology This review is intended to highlight the need to consider the effects of sex and sex in future studies of sarcoidosis Recent findings: The clinical manifestations of sarcoidosis differ based on sex and gender There is emerging evidence that female and male hormones and X-linked genes are important determinants of immune responses to environmental antigens, which has important implications for granuloma formation in the context of sarcoidosis Furthermore, sex hormone levels predictably change throughout adolescence and adulthood, and this occurs in parallel with the onset immune senescence and changes in physiology with advanced age Summary: Recent studies indicate that sex and age are important variables shaping the immune response of humans to environmental antigens We posit herein that sex and age are important determinants of sarcoidosis clinical phenotypes Many gaps in our understanding of the roles played by sex and gender in sarcoidosis, and these need to be considered in future studies